Pencegahan Tindak Perundungan Dan Kekerasan Di Sekolah Ditinjau Dari Aspek Psikologi Dan Hukum - Hawanti, Santhy; Dwiyanti, Retno; Hidayah, Astika Nurul (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
The issue of bullying has a severe impact on the mental and physical well-being of the victim, with fatal consequences such as severe depression or death. Parental influence is crucial in preventing bullying. Children tend to mimic their parents' attitudes and behaviours. Positive attitudes, empathy and tolerance from parents can encourage children to adopt these values. Parents who are actively involved and open to effective communication help children develop empathy and feel supported, making them more likely to report or seek help in bullying situations. Parents need to understand the psychological and legal aspects of bullying and school violence prevention to protect their children's well-being. Psychological knowledge helps recognise early signs of trauma and provide emotional support, as well as establishing the values of empathy, tolerance and respect in children. Legal knowledge enables parents to take appropriate action if their child is victimised, liaise with schools and authorities, and ensure anti-bullying policies are implemented. This regulation creates a safe and supportive environment for children to grow. Strengthening parents' understanding and knowledge of bullying prevention and its psychological and legal impacts was done through counselling activities. This counselling presented material on the psychological impact of bullying on children and the legal consequences for perpetrators and omission of bullying activities for both children and schools and parents. The counselling sessions were attended by parents, teachers, and school committees. The counselling participants said that after attending the training, their knowledge about bullying, its impact, and preventive measures improved. The results of the questionnaire before and after attending the counselling showed increased participants' understanding. Keywords: bullying; prevention; violence Abstrak: Perundungan dan kekerasan di sekolah berdampak parah pada perkembangan mental dan emosional anak serta mengganggu proses belajar mengajar. Data FSGI, pada periode Januari-Juli 2023 terdapat 16 kasus perundungan dengan 43 korban. Jumlah ini meningkat menjadi 23 kasus pada periode Januari-September 2023, dengan tingkat perundungan tertinggi terjadi di sekolah menengah pertama (SMP) yang mencapai 50%, bahkan 2 orang meninggal dunia selama periode tersebut SMP Muhammadiyah Kembaran juga menghadapi masalah ini. Untuk mencegah bullying dan kekerasan, diadakan penyuluhan dengan metode ceramah dan diskusi guna memberikan pemahaman komprehensif dan praktis. Kegiatan ini melibatkan guru dan orang tua untuk menciptakan lingkungan sekolah yang aman. Hasil penyuluhan menunjukkan peningkatan pemahaman dan kesadaran peserta tentang dampak negatif bullying dan kekerasan serta pentingnya peran setiap orang dalam pencegahannya, yang terbukti dari hasil kuesioner sebelum dan sesudah sesi penyuluhan.Kata kunci: kekerasan; perundungan; pencegahan